Improving Performance of Village Owned Enterprises: The Role of Human Capital, Organizational Culture, and Entrepreneurial Orientation - Yesi Mutia Basri; Natasya Agustina Br Pinem; Hariadi Yasni (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2021)
Village-owned enterprises (BUMDes) are economic institutions that have a strategic role in improving the village economy. However, BUMDes operational activities often face obstacles that cause BUMDes not to run as they should. This study aims to analyze the effect of human capital, organizational culture, and entrepreneurial orientation on the performance of BUMDES. The population in this study was 242 BUMDes scattered in Kampar Regency. The sampling technique used was purposive sampling by selecting active BUMDes. Respondents in this study were BUMDes managers. Of the 140 active BUMDes, 120 BUMDes participated in this research. The data collection technique uses a questionnaire that is distributed online via a google form. The results of data analysis using WarpPLS 7.0 show that human capital, organizational culture, and entrepreneurial orientation positively affect the performance of BUMDes. This research implied that knowledge and expertise possessed by managers and applying them will further improve the performance of BUMDes. It is also important for commitment, loyalty, and trying to give the best in implementing organizational culture. Creativity in innovating, being proactive, and having the courage to take risks and work hard are also crucial in managing BUMDes. Based on the research limitation, it is suggested that further research can expand the research area and use other variables that can affect the performance of BUMDes, such as innovation or leadership style.